Contribution of Limb Muscle Power, Flexibility of Limb Muscles and Self-Confidence to the Accuracy of Futsal Shooting - Anny Nur Hidayati; Sulaiman Sulaiman; Mugiyo Hartono (JUARA : Jurnal Olahraga, 2023)
The objectives of this study are 1) To analyze the contribution of limb muscle power to the accuracy of ball shooting in the women's futsal student activity unit in Semarang 2) To analyze the contribution of limb muscle flexibility to the accuracy of ball shooting in the women's futsal student activity unit in Semarang 3) To analyze the confident contribution to the accuracy of ball shooting in the women's futsal student activity unit in Semarang 4) To analyze the contribution of power and flexibility limb muscles against the accuracy of shooting the ball in the women's futsal student activity unit in Semarang. This research uses quantitative methods with a correlation design. The population in this study was the women's futsal activity unit at UPGRIS, UNNES, and UNISSULA. The sampling technique uses purposive sampling consisting of 70 female students. The results of this study: 1) Power of limb muscles contributes to the accuracy of ball shooting at Women's Futsal UKM in Semarang. 2) The flexibility of the limb muscles contributes to the accuracy of shooting the ball at the Women's Futsal UKM in Semarang. 3) Confidence contributes to the accuracy of ball shooting at the Women's Futsal UKM in Semarang. 4) Limb muscle power and limb muscle flexibility contribute to the accuracy of ball shooting at the Women's Futsal UKM in Semarang. Based on the study results, it can be concluded that there is a significant contribution between limb muscle power, limb muscle flexibility, and confidence in the accuracy of futsal shooting based on simultaneous regression tests.